Functional genome annotation by combined analysis across microarray studies of Trypanosoma brucei. - Hamed Shateri Najafabadi; Reza Salavati (Public Library of Science (PLoS), 2010)
BACKGROUND: Functional annotation of trypanosomatid genomes has been a daunting task due to the low similarity of their genes with annotated genes of other organisms. Three recent studies have provided gene expression profiles in several different conditions and life stages for one of the main disease-causing trypanosomatids, Trypanosoma brucei. These data can be used to study the gene functions and regulatory mechanisms in this organism. METHODOLOGY/PRINCIPAL FINDINGS: Combining the data from three different microarray studies of T. brucei, we show that functional linkages among T. brucei genes can be identified based on gene coexpression, leading to a powerful approach for gene function prediction. These predictions can be further improved by considering the expression profiles of orthologous genes from other trypanosomatids. Furthermore, gene expression profiles can be used to discover potential regulatory elements within 3' untranslated regions. CONCLUSIONS/SIGNIFICANCE: These results suggest that although trypanosomatids do not regulate genes at transcription level, trypanosomatid genes with related functions are coregulated post-transcriptionally via modulation of mRNA stability, implying the presence of complex regulatory networks in these organisms. Our analysis highlights the demand for a thorough transcript profiling of T. brucei genome in parallel with other trypanosomatid genomes, which can provide a powerful means to improve their functional annotation.